Conflict of Interest Policies at French Medical Schools: Starting from the Bottom. - Paul Scheffer; Christian Guy-Coichard; David Outh-Gauer; Zoéline Calet-Froissart; Mathilde Boursier; Barbara Mintzes; Jean-Sébastien Borde (PLoS ONE, 2017)
Medical faculties have a role in ensuring that their students are protected from undue commercial influence during their training, and are educated about professional-industry interactions. In North America, many medical faculties have introduced more stringent conflict of interest (COI) policies during the last decade. We asked whether similar steps had been taken in France. We hypothesized that such policies may have been introduced following a 2009-2010 drug safety scandal (benfluorex, Mediator) in which COIs in medicine received prominent press attention.We searched the websites of all 37 French Faculties of Medicine in May 2015 for COI policies and curriculum, using standardized keyword searches. We also surveyed all deans of medicine on institutional COI policies and curriculum, based on criteria developed in similar US and Canadian surveys. Personal contacts were also consulted. We calculated a summary score per faculty based on 13 criteria. [range 0-26; higher scores denoting stronger policies].In total, we found that 9/37 (24%) of French medical schools had either introduced related curriculum or implemented a COI-related policy. Of these, only 1 (2.5%) had restrictive policies for any category. No official COI policies were found at any of the schools. However, at 2 (5%), informal policies were reported. The maximum score per faculty was 5/26, with 28 (76%) scoring 0.This is the first survey in France to examine COI policies at medical faculties. We found little evidence that protection of medical students from undue commercial influence is a priority, either through institutional policies or education. This is despite national transparency legislation on industry financing of health professionals and limits on gifts. The French National Medical Students Association (ANEMF) has called for more attention to COI in medical education; our results strongly support such a call.